An investigation into the railway ballast dielectric properties using different GPR antennas and frequency systems. (January 2018) - Tosti, Fabio; Bianchini Ciampoli, Luca; Calvi, Alessandro; Alani, Amir M.; Benedetto, Andrea
Abstract: This paper presents an investigation into the relative dielectric permittivity of railway ballast using ground-penetrating radar (GPR). To this effect, the experimental tests are carried out using a container (methacrylate material) of dimensions 1.5 × 1.5 × 0.5 m. GPR systems equipped with different ground-coupled and air-coupled antennas and central frequencies of 600 MH, 1000 MHz, 1600 MHz and 2000 MHz (standard and low-powered antenna systems) are used for testing purposes. Several processing methods are applied to assess and compare the dielectric permittivity of the ballast system under investigation. A comparison of the results identifies critical factors as well as antennas and central frequencies most suitable for the purpose. Highlights: Non-destructive assessment of the electromagnetic properties of railway ballast aggregates. Use of different GPR antennas and frequency systems within a unique experimental (laboratory) setup. Identify critical factors as well as antennas and central frequencies most suitable for the investigation of railway ballast.